Capital structure, wage bargaining and employment - Erkki Koskela; Rune Stenbacka (Bank of Finland, 2000)
We offer a unified framework to analyze the determination of employment, employee effort, wages, profit sharing and capital structure when firms face stochastic revenue shocks.We apply a generalized Nash bargaining solution, which extends the wage bargaining literature by incorporating efficiency wage considerations, profit sharing and capital structure.The profit sharing instrument is demonstrated to have positive effort-augmenting and wage-moderating effects, which exactly offset the negative dilution effect in equilibrium.Leverage is shown to reduce employment and to have a strategic commitment value as a wage-moderating mechanism for firms facing unions in bilateral wage negotiations.Finally, some implications for equilibrium unemployment are discussed.
URN:NBN:fi:bof-20140807168
Keywords: 330; wage bargaining; profit sharing; capital structure; employment